BIOACTIVE COMPOUNDS IN COCOS NUCIFERA L. WATER: A PROTECTIVE SHIELD FOR EPIDIDYMIS AGAINSTBISPHENOLA-INDUCEDOXIDATIVESTRESSINSPRAGUEDAWLEYRATS - Nur Farah Shafinaz Shafie; Nurul Kabir; Nor Azlina Abd Aziz; Noor Hashida Hashim (Journal of Animal and Plant Sciences, 2026)
Bisphenol A (BPA) is a prevalent endocrine disruptor which poses a serious risk to male reproductive health by inducing oxidative stress. Evidence links BPA exposure to impaired spermatogenesis, altered testicular morphology, and disrupted steroidogenesis. In contrast, its effects on the epididymis remain less clearly defined, highlighting the need for further investigation. While various strategies have been explored to counteract BPA- induced toxicity, natural interventions targeting the male reproductive system are still underexplored. Notably, Cocos nucifera L. (coconut) water, rich in polyphenols and bioactive compounds, is known for its antioxidative properties. This study investigates the oxidative stress and histopathological changes underlying BPA-induced epididymal damage and evaluates the protective potential of coconut water in counteracting these effects. Thirty Sprague-Dawley rats were allocated into five groups: control (C) received 0.5 mL of distilled water per day, vehicle (V) received 0.5 mL of corn oil per day, BPA (B) received 50 mg/kg per day, coconut water (CW) received 10 mL/kg per day, and co-administration of BPA and coconut water (CW+B) received both coconut water and BPA. The epididymides were harvested on day 31 for oxidative stress analysis and histological examination. BPA administration reduced glutathione levels, increased malondialdehyde levels, and induced histological alterations in the epididymis (p < 0.001). However, these parameters were significantly enhanced by the coconut water administration in CW+B group (p < 0.001). Conclusively, this study suggests that coconut water boosts antioxidant defences in rat epididymal tissue, offering protection against BPA-mediated harm.
Keywords: coconut water; bisphenol A; epididymis; oxidative stress; antioxidant